Characterizing ionospheric perturbations with refined gradient ionosphere indices - Norbert Jakowski; M. Mainul Hoque; Juan Andrés Cahuasquí; Grzegorz Nykiel (GPS Solutions, 2026)
Precision and safety-critical Global Navigation Satellite System (GNSS) applications require high-fidelity monitoring of space weather conditions, particularly ionospheric disturbances. These systems are highly sensitive to sharp spatial gradients and rapid Total Electron Content (TEC) variations. To support both operational and scientific needs, this study proposes and evaluates two variants of the Gradient Ionosphere indeX (GIX): GIXM and GIXV. Derived from absolute TEC measurements at pairs of ionospheric piercing points (IPPs), the GIX quantifies gradients by dividing the TEC difference by the distance between IPPs. The GIXM method calculates the scalar average of these gradients, while GIXV computes the resultant gradient vector over regional scales (typically ≥ 500 × 500 km 2 ) to capture both magnitude and direction. Comparative analysis reveals a strong correlation between GIXM and the operational geodetic I95 index, confirming GIXM’s utility for disturbance scaling and reliability assessment. Accurate estimation of the GIXV vector requires sufficient spatial coverage, typically involving 35–45 IPPs. Furthermore, analyzing GIX dynamics within the Magnetosphere-Ionosphere-Thermosphere (MIT) framework demonstrates potential for predictive modeling. By tracking the equatorward propagation of high-latitude gradient structures, this framework enables the forecasting of GIXM I95 levels, offering a robust tool for mitigating GNSS risks.

A cross-sectional view of the drinking water scenario in a climate-stressed setting: Case study from southwestern Bangladesh - Tasneem Chowdhury Fahim; Md Mainul Islam; Zinat Hasiba; Md. Ahasanul Hoque (Utilities Policy, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Ghrelin-disrupting activity of arsenic and its relation to cardiometabolic diseases - Kamrun Nahar Rossi; Faysal Abedin; Nayan Chandra Mohanto; Biplob Ahmed; Sobuj Mia; Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; Ahsanul Mahbub Jubayar; et al. (Toxicology and Applied Pharmacology, 2026)

Association between Arsenic Exposure and CCL5: its Implications in Asthma and Skin Lesions - Osman Goni; Nesar Uddin; Rajoana Karim Rimi; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Sharon Jahan Sarder; Junayed Sadi; Mainul Islam; Victor Mondal; K M Ahsanul Kabir; Abu Eabrahim Siddique; et al. (Exposure and Health, 2026)

Grazing-angle ionospheric delays observed during the GNSS-R PRETTY mission - Mario Moreno; Maximilian Semmling; Florian Zus; Georges Stienne; Andreas Dielacher; Mainul Hoque; Jens Wickert; Hossein Nahavandchi (Journal of Geodesy, 2025)
Spaceborne GNSS reflectometry (GNSS-R) has emerged as a valuable technique for surface and atmospheric remote sensing, particularly under grazing-angle geometries where atmospheric effects are amplified. Single-frequency missions such as ESA passive REflecTomeTry and dosimetrY (PRETTY) rely on model-based corrections to account for ionospheric and tropospheric delays. In this study, we exploit PRETTY’s capabilities to perform observations down to 1 degree (at the specular point) to investigate ionospheric effects at very low angles. We analyze six GNSS-R events recorded over the North Polar region in July 2024, focusing on the estimation of the relative ionospheric delay using code delay observations. Comparisons with model-based ionospheric delays from NEDM2020, NeQuick, and IRI show close agreement, with NEDM2020 consistently exhibiting the lowest residual differences, ranging from 1.28 to 4.39 m across all events. This supports the ability of GNSS-R code delay observables to capture the first-order ionospheric delay with reasonable fidelity. Uncertainty analysis reveals that the observed delay fitting process dominates the overall error budget, with additional contributions from tropospheric correction and surface height uncertainty. Furthermore, inversion of the fitted delays using the Chapman layer model yields plausible F-layer parameters, with peak heights ranging from 307 to 367 km and a mean delay RMSE of approximately 1.2 m (~ 4 TECU). Comparisons with ionosonde and EISCAT measurements show differences within ± 15 km. These results demonstrate the potential of single-frequency GNSS-R missions for retrieving ionospheric structure, particularly in remote regions where conventional techniques are limited or unavailable.

Relationship of fractalkine with arsenic exposure and the risk of cardiovascular diseases - Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Nayan Chandra Mohanto; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Biplob Ahmed; Sobuj Mia; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; et al. (Environmental Toxicology and Pharmacology, 2025)

Deep learning approach for combining global ionospheric maps for GNSS positioning - Mateusz Poniatowski; Grzegorz Nykiel; Mohammed Mainul Hoque; Jȩdrzej Szmytkowski (GPS Solutions, 2025)

Dynamics of gas dispersion in a rising bubble plume in presence of surfactant - Abdullaziz Glabe Zakari; Mohammad Mainul Hoque; Peter Ireland; Geoffrey Evans; Subhasish Mitra (Minerals Engineering, 2025)

Ionospheric tomography for SWARM satellite orbit determination using single-frequency GNSS data - Fabricio S. Prol; Alessio Pignalberi; Artem Smirnov; Michael Pezzopane; Ana L. Christovam; Kannan Selvan; Mainul Hoque; Sanna Kaasalainen (GPS Solutions, 2025)
Ionospheric tomography offers three-dimensional (3D) description of the electron density distribution, enabling the direct incorporation of electron density data into the slant total electron content (STEC) computation. As a result, STEC derived from tomography helps mitigate the ionospheric delay experienced in the line of sight between global navigation satellite systems (GNSS) and satellites positioned in low Earth orbits (LEO). Tomography can therefore be effectively employed to correct single-frequency GNSS observations and allow enhanced positioning of spaceborne platforms. We demonstrate the accuracy and performance of a global-scale ionospheric tomography method for determining satellite orbits, utilizing single-frequency GNSS measurements combined with a precise point positioning (PPP) algorithm. We compare the tomographic outcomes against orbit determination derived from the GRoup and PHase ionospheric correction (GRAPHIC) observable and based on an ionospheric climatological model. Near the peak of solar cycle 24, the overall accuracy achieved with tomography was around 3.8 m. notably, compared to the background climatological model, tomography demonstrated improvements ranging from 15 to 20%. The GRAPHIC method outperformed tomography, achieving an accuracy of 0.7 m, whereas we obtained around 7 m accuracy when no ionospheric model is employed. Although the developed ionospheric tomography has yet to match the precision of GRAPHIC, our results bring us relatively closer to this objective.

Relationship between GIX, SIDX, and ROTI ionospheric indices and GNSS precise positioning results under geomagnetic storms - Grzegorz Nykiel; Juan Andrés Cahuasquí; Mohammed Mainul Hoque; Norbert Jakowski (GPS Solutions, 2024)
Ionospheric indices give information about ionospheric perturbations, which may cause absorption, diffraction, refraction, and scattering of radio signals, including those from global navigation satellite systems (GNSS). Therefore, there may be a relationship between index values and GNSS positioning results. A thorough understanding of ionospheric indices and their relationship to positioning results can help monitor and forecast the reliability and accuracy of GNSS positioning and support the precision and safety of life applications. In this study, we present the relationship between three indices: Gradient Ionosphere indeX (GIX), Sudden Ionospheric Disturbance indeX (SIDX), and Rate of Total electron content Index (ROTI) in relation to precise positioning results. We used two approaches: precise point positioning (PPP) and relative positioning for long baselines. We focus on GNSS stations located in Europe for two selected geomagnetic storms: March 17, 2015, and May 22, 2015. Our results show that in the case of PPP, positioning degradation occurred mainly at high latitudes and was mostly caused by rapid small-scale changes in ionospheric electron content represented by SIDX and ROTI. We also showed a significant correlation between cycle slips of GNSS signals and ROTI (0.88). The most significant degradations for relative positioning for low and medium latitudes were associated with large spatial gradients reflected by the GIX.

Seasonal morphology and solar activity dependence analysis of mid-latitude post-midnight enhancement using Global Ionospheric Map - Eman M. El-Desoky; Mohammed Mainul Hoque; M. Youssef; Ayman Mahrous (Advances in Space Research, 2024)

Ionosphere variability II: Advances in theory and modeling - Ioanna Tsagouri; David R. Themens; Anna Belehaki; Ja-Soon Shim; Mainul M. Hoque; Grzegorz Nykiel; Claudia Borries; Anna Morozova; Teresa Barata; Wojciech J. Miloch (Advances in Space Research, 2023)

Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Influence of bubble surface loading on particle-laden bubble rising dynamics in a fluid flow system - Mohammad Mainul Hoque; Zhengbiao Peng; Geoffrey Evans; Elham Doroodchi (Minerals Engineering, 2023)

Positioning performance of the Neustrelitz total electron content model driven by Galileo Az coefficients - Juan Andrés Cahuasquí; Mohammed Mainul Hoque; Norbert Jakowski (GPS Solutions, 2022)
To aid single-frequency GNSS users, the Neustrelitz Total Electron Content Model (NTCM) has been proposed as an adequate solution to mitigate propagation errors besides the GPS Klobuchar and Galileo NeQuick models. Using the three effective ionization coefficients broadcast in the Galileo navigation message as driver parameters, the version NTCM-GlAzpar, in general, performs equal to or better than NeQuickG when compared to the total electron content domain. In this work, we performed a global statistical validation of the NTCM-GlAzpar model in the position domain by comparing its results with the results of the Klobuchar and NeQuickG models for the first time. For this purpose, we used the GNSS analysis tool gLAB and its customization capabilities in the Standard Point Positioning mode. The data used for model validation correspond to a one-month period of perturbed solar and geomagnetic activity (December 2014) and another one-month period of quiet conditions (December 2019). The data have a worldwide coverage with up to 73 IGS stations. The statistical analysis of the hourly average 3D position error shows that the root mean squared (RMS) values of the Klobuchar model are 6.71 and 2.75 m for the perturbed and quiet conditions, respectively, whereas the NeQuickG model has RMS values of 4.61 and 2.35 m. In comparison, the corresponding RMS values of 4.36 and 2.32 m of the NTCM-GlAzpar model confirm its better positioning performance for both periods. However, we identify also that the performance of NTCM-GlAzpar slightly worsens toward higher latitudes and at night local time. Simple software adaptations and a low computational cost make NTCM-GlAzpar an alternative practicable algorithm to improve the accuracy of GNSS single-frequency applications.

A new method to estimate GPS satellite and receiver differential code biases using a network of LEO satellites - Liangliang Yuan; Mainul Hoque; Shuanggen Jin (GPS Solutions, 2021)
The differential code biases (DCBs) of the global positioning system (GPS) receiver onboard low-Earth orbit (LEO) satellites are commonly estimated by a local spherical symmetry assumption together with the known GPS satellite DCBs from ground-based observations. Nowadays, more and more LEO satellites are equipped with GPS receivers for precise orbit determination, which provides a unique chance to estimate both satellite and receiver DCBs without any ground data. A new method to estimate the GPS satellite and receiver DCBs using a network of LEO receivers is proposed. A multi-layer mapping function (MF) is used to combine multi-LEO satellite data at varying orbit heights. First, model simulations are conducted to compare the vertical total electron content (VTEC) derived from the multi-layer MF and the reference VTEC obtained from the empirical ionosphere model International Reference Ionosphere and Global Core Plasmasphere Model. Second, GPS data are collected from five LEO missions, including ten receivers used to estimate both the satellite and receiver DCBs simultaneously with the multi-layer MF. The results show that the GPS satellite DCB solutions obtained from space-based data are consistent with ground-based solutions provided by the Centre for Orbit Determination in Europe. The proposed normalization procedure combining topside observations from different LEO missions has the potential to improve the accuracies of satellite DCBs of Global Navigation Satellite Systems as well as the receiver DCBs onboard LEO satellites, although the number of LEO missions and spatial–temporal coverage of topside observations are limited.

Ionospheric VTEC and satellite DCB estimated from single-frequency BDS observations with multi-layer mapping function - Ke Su; Shuanggen Jin; J. Jiang; Mainul Hoque; Liangliang Yuan (GPS Solutions, 2021)

Estimation of LEO-GPS receiver differential code bias based on inequality constrained least square and multi-layer mapping function - Liangliang Yuan; Shuanggen Jin; Mainul Hoque (GPS Solutions, 2020)

Fast ionospheric correction using Galileo Az coefficients and the NTCM model - Mohammed Mainul Hoque; Norbert Jakowski; Raul Orús-Pérez (GPS Solutions, 2019)

On the estimation of higher-order ionospheric effects in precise point positioning - Simon Banville; Rafal Sieradzki; Mainul Hoque; Kinga Wezka; Tomasz Hadas (GPS Solutions, 2017)

Mitigation of higher order ionospheric effects on GNSS users in Europe - M. Mainul Hoque; N. Jakowski (GPS Solutions, 2008)

Higher order ionospheric effects in precise GNSS positioning - M. Mainul Hoque; N. Jakowski (Journal of Geodesy, 2007)